The Geographic Spread of COVID-19 Correlates with Structure of Social Networks as Measured by Facebook - Theresa Kuchler; Dominic Russel; Johannes Stroebel (Center for Economic Studies and ifo Institute (CESifo), 2020)
We use anonymized and aggregated data from Facebook to show that areas with stronger social ties to two early COVID-19 "hotspots" (Westchester County, NY, in the U.S. and Lodi province in Italy) generally have more confirmed COVID-19 cases as of March 30, 2020. These relationships hold after controlling for geographic distance to the hotspots as well as for the income and population density of the regions. These results suggest that data from online social networks may prove useful to epidemiologists and others hoping to forecast the spread of communicable diseases such as COVID-19.
Keywords: C60; I10; 330; social connectedness; COVID-19; coronavirus; communicable disease